2021
DOI: 10.1007/s12195-021-00696-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Structural Proteins Exposure Alter Thrombotic and Inflammatory Responses in Human Endothelial Cells

Abstract: Introduction We have experienced a pandemic induced by the interaction of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) structural proteins with innate structures. These interactions are especially prevalent for patients with underlying pathologies, such as cardiovascular diseases. However, there has been limited work to uncover the range of responses induced by SARS-CoV-2 structural proteins. Thus, our objective was to investigate how endothelial cell pro-thrombotic and pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…They reported a specific proteomic signature of strongly regulated proteins in both critically and non-critically ill patients, compared to healthy subjects, including proteins involved in the acute phase response (C-reactive protein [CRP], serum amyloid A, and ferritin), immune-response (C1R, C4A/C4B, MBL2 and SERPING1), and coagulation (proteins of the intrinsic and extrinsic coagulation cascade, Kininogen-1), and reported that the C1r complement subcomponent is highly associated with disease severity, with an AUC of 0.93 (sensitivity: 89%; specificity: 82%). Consistent with the above findings, Freda et al [ 83 ] observed significant increases in thrombotic and inflammatory marker expression (thrombomodulin, PECAM-1) in human endothelial cells exposed to SARS-CoV-2 structural proteins. Kaiser et al [ 84 ] analyzed the proteome of neutrophils in severe COVID-19 and reported a unique proteomic signature of increased IL-8 secretion associated with increased D-dimer and neutrophil extracellular trap (NET) production, elevated complement factors (C1R, C1S, C5, C6, C7, C8 and C9), and fibrinogen binding, further uncovering a procoagulant role of inflammation and complement pathways.…”
Section: The Role Of Complement In Covid-19 Induced Thrombotic Microa...supporting
confidence: 67%
“…They reported a specific proteomic signature of strongly regulated proteins in both critically and non-critically ill patients, compared to healthy subjects, including proteins involved in the acute phase response (C-reactive protein [CRP], serum amyloid A, and ferritin), immune-response (C1R, C4A/C4B, MBL2 and SERPING1), and coagulation (proteins of the intrinsic and extrinsic coagulation cascade, Kininogen-1), and reported that the C1r complement subcomponent is highly associated with disease severity, with an AUC of 0.93 (sensitivity: 89%; specificity: 82%). Consistent with the above findings, Freda et al [ 83 ] observed significant increases in thrombotic and inflammatory marker expression (thrombomodulin, PECAM-1) in human endothelial cells exposed to SARS-CoV-2 structural proteins. Kaiser et al [ 84 ] analyzed the proteome of neutrophils in severe COVID-19 and reported a unique proteomic signature of increased IL-8 secretion associated with increased D-dimer and neutrophil extracellular trap (NET) production, elevated complement factors (C1R, C1S, C5, C6, C7, C8 and C9), and fibrinogen binding, further uncovering a procoagulant role of inflammation and complement pathways.…”
Section: The Role Of Complement In Covid-19 Induced Thrombotic Microa...supporting
confidence: 67%
“…At different levels in the pathogenesis of COVID-19, Cx43 hemichannels can be involved in the initiation and dissemination of inflammatory processes. Recently, it was reported that Cx43 expression levels in human epithelial cells are upregulated upon exposure to SARS-CoV-2 [51]. SARS-CoV-2 starts causing damage to the cells at the pulmonary level, where the virus infects alveolar type II cells and alveolar macrophages, resulting in pneumonia and acute respiratory distress syndrome [12,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet adhesion, activation, and aggregation play a pivotal role in thrombosis, which is a hallmark of severe COVID-19 [ 14 , 22 , 61 ]. An essential component in the platelet activation process is the interaction of adenosine diphosphate with the platelet P2Y12 receptor [ 13 , 62 , 63 ].…”
Section: P2y12 Inhibitorsmentioning
confidence: 99%